A case study of corporate social responsibility by Malaysian government link company - Abdul Hamid, Fathilatul Zakimi; Atan, Ruhaya; Md Saleh, Md Suhaimi (Elsevier Ltd., 2014)
The objective of the study is to investigate the CSR practice by the one of the Malaysian Government Link Company via case study approach.As a GLC's the business has to balance its profit with social responsibility to the state and society.According to the literature in modern era of CSR, the business social responsibility starts when the business determines their act in economic and social obligation.The result of the study shows that the business CSR initiative has changed from altruistic to its core competency.Furthermore, its revise CSR agenda has contributed to the state socio-economic development as suggested by the Father of Social Responsibility on the business social obligation postulate.